2016
DOI: 10.1007/s10900-016-0270-y
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Survey on the Dengue Knowledge, Attitudes and Preventive Practices Among Students and Staff of a Public University in Malaysia

Abstract: Abstract:Behavioural impact programmes are especially effective for dengue control and prevention. Universities are key settings for health promotion, so understanding factors that influence the practice of dengue prevention within a university community becomes important. This study aimed to examine the factors affecting dengue knowledge, attitude and preventive practices amongst students and staff of a public university. A cross-sectional survey study was conducted in Kuala Lumpur, Malaysia. A total of 372 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 21 publications
7
40
0
2
Order By: Relevance
“…Most studies on leptospirosis KAP were descriptive and did not tried to identify factors that may influence the predisposition to use preventive practices [ 9 , 33 , 35 , 37 , 44 , 65 ]. Our results are consistent with those of Arbiol et al [ 32 ], Lau et al [ 7 ] and other studies regarding zoonotic disease prevention practices that show that greater knowledge about the disease results in a greater adoption of preventive practices [ 31 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most studies on leptospirosis KAP were descriptive and did not tried to identify factors that may influence the predisposition to use preventive practices [ 9 , 33 , 35 , 37 , 44 , 65 ]. Our results are consistent with those of Arbiol et al [ 32 ], Lau et al [ 7 ] and other studies regarding zoonotic disease prevention practices that show that greater knowledge about the disease results in a greater adoption of preventive practices [ 31 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Assessments of people’s knowledge of leptospirosis and health behavior provide critical information for disease prevention [ 9 , 31 35 ]. In particular, surveys of knowledge, attitudes and practices (KAP) are useful public health tools to identify effective strategies for behavior change towards safer practices [ 32 , 33 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that knowledge was positively related to dengue prevention practices. This finding is similar to previous research in Malaysia that knowledge is significantly and positively related to dengue prevention practices (Lugova and Wallis, 2017). This finding is also similar to the results of a household survey in urban areas in Yemen that knowledge is related to dengue prevention practices (Alyousefi, et al, 2016).…”
Section: Implementation Of Dengue Prevention and Related Factorssupporting
confidence: 91%
“…Knowledge, attitude and implementation of dengue prevention were categorized as good and not good. The cut-off reaches more than 75% of the total score for good categories (Lugova and Wallis, 2017). Whereas for the descriptive purposes, it was divided into three categories, namely poor (score <60%), moderate (score 60-75%), and good (score> 75%).…”
Section: Methodsmentioning
confidence: 99%
“…Results of previous Malaysian studies showed that the urban/suburban communities generally have good knowledge of dengue and its symptoms and positive attitude on dengue prevention, but these are not translated to good practice in dengue prevention 25,[30][31][32] . However, there are other studies which demonstrated various levels of KAP different from those reported above 26,28,33 , with few others citing good dengue prevention practices among the urban/suburban communities 24,34,35 . This KAP study revealed that only half of the study population has exemplary and adequate knowledge regarding dengue.…”
Section: Discussionmentioning
confidence: 80%